Centrality Bias in Inter-City Trade - Tomoya Mori; Jens Wrona (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Large cities (central places) excessively export to smaller cities in their surrounding hinterland. Using Japanese inter-city trade data, we identify a substantial centrality bias: Shipments from central places to their hinterland are 50%-125% larger than predicted by gravity forces. This upward bias stems from aggregating across industries, which are hierarchically distributed across large and small cities, and therefore does not arise in sectoral gravity estimations. When decomposing the centrality bias along the margins of our data, we find that the by far largest part of this aggregation bias can be attributed to the extensive industry margin.
Keywords: C43; F10; F12; F14; R12; 330; Inter-city trade; central place theory; gravity equation; aggregation bias